KUALITAS PELAYANAN PEMBUATAN KARTU IDENTITAS ANAK (KIA) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR - Noviana Ratna Nagari; Joko Suranto (Solidaritas, 2020)
Karanganyar Regency’s Population and Civil Registration Office is the regional apparatus that responsible and authorized to carry out service in the area of population and civil registration. One of them is the making the Child Identity Card (KIA) as an effort by the government to protect and grant children’s rights. This type of research is descriptive qualitative. Data collection techniques used included (1) interviews, (2) observations, (3) documentation. In this study researchers measured the quality of service using the theory of Parasuraman, Zeithmal, and Berry, the results of research on the quality of KIA manufacturing services at the Population and Civil Registry Service in Karanganyar Regency can be said good enough, this can be seen with the results of the study as follows: (1) tangibles, the facilities in the waiting room are further improved and inadequate parking lots, (2) reliability has been said to be good, (3) responsiveness has generally been said to be good, (4) assurance has been said to be good and the community is satisfied with the services provided, but there are some obtstacles such as the card runs out, (5) emphaty, there are employees who are not friendly, polite and polite when the service is busy. Keywords: Quality, Service, KIA